2022
DOI: 10.3389/fpsyg.2022.849528
|View full text |Cite
|
Sign up to set email alerts
|

The Construction of Interactive Teaching Quality Monitoring System From the Perspective of Psychology

Abstract: The article first proposes a reflection on the status quo of classroom teaching in public universities, selects a large number of educational scenes, and analyzes these selected educational concepts in detail from a theoretical perspective. Through the establishment of a teaching quality monitoring system based on careful observation and analysis, several major problems in public university classrooms have been discovered: poor classroom interaction mode, single classroom interaction mode, low classroom intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Our results are congruent with the strategies for measuring didactic interactions that complement different approaches to evaluate the quality of instruction [11,[13][14][15] and teacher performance in natural classroom interaction scenarios [12]. In this sense, although it is true that the use of self-reports has been widespread when evaluating teacher performance, teacher behaviors have been traditionally assessed in isolation or independently from the assessment of student didactic performance, despite the fact that they relate to the same interactive situations in which the teacher is said to deploy the assessed teaching behaviors.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our results are congruent with the strategies for measuring didactic interactions that complement different approaches to evaluate the quality of instruction [11,[13][14][15] and teacher performance in natural classroom interaction scenarios [12]. In this sense, although it is true that the use of self-reports has been widespread when evaluating teacher performance, teacher behaviors have been traditionally assessed in isolation or independently from the assessment of student didactic performance, despite the fact that they relate to the same interactive situations in which the teacher is said to deploy the assessed teaching behaviors.…”
Section: Discussionsupporting
confidence: 84%
“…Before the virtualization of classes across the world in the university context due to the SARS-CoV-19 pandemic, there was already great interest in the study of teacher and student performance during didactic interactions [11][12][13][14]. Research on the subject has shown that various aspects of the didactic interaction in face-to-face classes have affected the quality of instruction, the quality of learning and the academic achievement of students and has shown a low efficiency in terms of classroom interaction and an inefficiency in terms of the feedback of classroom interaction [9,[11][12][13][14]. On the other hand, it has been reported that classes in smart classrooms have a better effect on teacher-student interaction in contrast with classes in traditional multimedia classrooms [15].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of information teaching and the establishment of network teaching platforms, education is likely to move gradually from single-mode to multi-modal, and implementing multi-modal teaching will become an inevitable trend in educational development [72,73]. In information teaching, multi-modal education, in an interactive way, applies to teaching subjects and objects, such as the interaction between students and problem situations and interactions with teachers and the network environment [74,75].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, interactive teaching also needs the support of multimedia technology and teaching tools to enhance the interest of classroom teaching and enhance students' sense of participation and experience. From the perspective of teaching practice, especially emphasizing the main role of students, improving the level of classroom interaction to promote the integration of teacher-student relationship, creating conditions for classroom interaction, and then improving the control ability of teacher-student interaction to enhance students' interactive language ability [17]. In addition, interactive teaching also requires teachers to have good teaching design and practical abilities, to develop scientific and effective teaching plans according to students' needs and learning characteristics, and to motivate students to actively participate in classroom activities.…”
Section: B Interactive Teaching Activities Function To Achieve Subjec...mentioning
confidence: 99%